Genotyping of Phytophthora infestans in eastern-Africa reveals a dominating invasive European lineage - Njoroge, A.W.; Andersson, B.; Lees, A.K.; Mutai, C.; Forbes, G.; Yuen, J.; Pelle, Roger (Scientific Societies, 2019)
Strains of Phytophthora infestans, the pathogen causing late blight of potato and tomato, are thought to be moved around the world through infected planting material. Since its first appearance in 1941, late blight has caused important losses to potato production in the eastern-Africa region (EAR). In the current study, the genetic structure of the population in Kenya, Uganda, Tanzania, Burundi and Rwanda was characterized using 12-plex microsatellite markers with the aim of testing the hypothesis that, a strain originating from Europe, 2_A1, has recently dominated the population in EAR. Analyses of 1,093 potato and 165 tomato samples collected between 2013 and 2016 revealed the dominance on potato in all countries of the 2_A1 clonal lineage. On tomato, a host-specialized form of the US-1 appears to persist in Rwanda, Uganda, and Tanzania, while in Kenya most samples from tomato (72.5%) were 2_A1. The US-1 lineage in Tanzania had two private alleles at the Pi02 marker, suggesting a possible independent introduction into the region. US-1 had higher genetic variability than 2_A1, consistent with the earlier establishment of the former. Continuous tracking of P. infestans population changes should help identify new virulent and aggressive strains, which would inform strategic disease management options.